The Validity of the Group Investigation Learning Model Documentary Film Media Assisted to Improve Students' Attitudes of Nationalism - Sri Nenowati; Idawati I; Azis Muslimin (Indonesian Journal of Primary Education, 2021)
The purpose of this study was to analyze the validity of the group investigation learning model assisted by documentary film media to increase student nationalism in social science learning. Research and development uses the ADDIE development model which consists of five stages, namely the analysis, design, development, implementation, and evaluation stages. The validity test was carried out after the analysis and design stages. The research instrument in this study was a validity assessment sheet given to three validators, namely two expert validators in the field of Social Sciences and one practitioner validator. Validation analysis was used using the percentage formula. The learning model is said to be valid if the percentage of total validity is at a valid level of 70%-80%. Based on the analysis, the percentage of total validity of the group investigation learning model assisted by documentary film media is 81.24%. This shows that the group investigation learning model assisted by documentary film media is valid and can be applied in the classroom.